2018
DOI: 10.3389/fpls.2018.00857
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiles of Sugarcane Culm Reveal the Relationship Among Metabolism and Axillary Bud Outgrowth in Genetically Related Sugarcane Commercial Cultivars

Abstract: Metabolic composition is known to exert influence on several important agronomic traits, and metabolomics, which represents the chemical composition in a cell, has long been recognized as a powerful tool for bridging phenotype–genotype interactions. In this work, sixteen truly representative sugarcane Brazilian varieties were selected to explore the metabolic networks in buds and culms, the tissues involved in the vegetative propagation of this species. Due to the fact that bud sprouting is a key trait determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 108 publications
1
16
0
Order By: Relevance
“…Sugars are well known to promote bud outgrowth in many species (Leduc et al, 2014; Rameau et al, 2015; Kebrom, 2017; Tarancón et al, 2017; Ferreira et al, 2018), and the relationship between sugars and bud outgrowth has been investigated for years (Maurel et al, 2004; Chao et al, 2007; Girault et al, 2010; Kebrom et al, 2010, 2012; Henry et al, 2011; Rabot et al, 2012; Mason et al, 2014; Barbier et al, 2015; Fichtner et al, 2017). Sugar effects are seemingly dependent on environmental conditions (Corot et al, 2017).…”
Section: Brc1 Is Regulated By Nutrientsmentioning
confidence: 99%
“…Sugars are well known to promote bud outgrowth in many species (Leduc et al, 2014; Rameau et al, 2015; Kebrom, 2017; Tarancón et al, 2017; Ferreira et al, 2018), and the relationship between sugars and bud outgrowth has been investigated for years (Maurel et al, 2004; Chao et al, 2007; Girault et al, 2010; Kebrom et al, 2010, 2012; Henry et al, 2011; Rabot et al, 2012; Mason et al, 2014; Barbier et al, 2015; Fichtner et al, 2017). Sugar effects are seemingly dependent on environmental conditions (Corot et al, 2017).…”
Section: Brc1 Is Regulated By Nutrientsmentioning
confidence: 99%
“…The highest number of metabolites were present in the leaves and decreased down the stem ( Figure 5) which agree with previous metabolomics studies conducted on sugarcane tissue (Glassop et al, 2007). Interestingly, a relatively higher number of metabolites were reported in the current study in comparison to other untargeted sugarcane metabolomics studies in the literature (Bosch et al, 2003;Ferreira et al, 2018;Glassop et al, 2007), thus, contributing to knowledge gaps regarding the sugarcane metabolome and presenting an improved method for conducting sugarcane metabolomics studies.…”
Section: The Exploration Of the Sugarcane Metabolome Highlights The Msupporting
confidence: 90%
“…A metabolomics study done on the SP80-3280 variety using GC-MS reported the presence of 70 metabolites in the +1 leaf tissue including sugars, alcohols, phenols, amino acids, organic acids, inorganic and fatty acids (Ribeiro et al, 2012). Similarly, the use of GC-MS by Ferreira et al (2018) for the metabolic profiling of sugarcane culm and bud tissues allowed for the isolation and These metabolite numbers reported are still far below the estimated number of structurally and biologically diverse plant metabolites of between 200,000 and 1 milion (Dixon & Strack, 2003;Fang et al, 2019;Rai et al, 2017).…”
Section: Sugarcane Metabolomics Studiesmentioning
confidence: 99%
“…The 100 μl of the organic phase was dried and derivatized as previously described (Roessner et al, 2001). 1 μl of the derivatized samples were analyzed on a Combi-PAL autosampler (Agilent Technologies) coupled to an Agilent 7890 gas chromatograph coupled to a Leco Pegasus 2 time-of-flight mass spectrometer (LECO, St. Joseph, MI, USA) in both split (1:40) and splitless modes (Weckwerth et al, 2004;Ferreira et al, 2018). Chromatograms were exported from Leco ChromaTOF software (version 3.25) to R software.…”
Section: Metabolomementioning
confidence: 99%